SELF-REGULATORY BODY YANG IDEAL UNTUK MEMPERKUAT INDEPENDENSI KOMISI PEMBERANTASAN KORUPSI - Paramitha, Dorothea Ansella Hana; Husodo, Jadmiko Anom (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2023)
This study aims to analyze the strengthening of the KPK as a law enforcement agency with independent principles through self-regulatory body. This research is a normative legal research using secondary data in the form of primary and secondary legal materials. The data collection technique was carried out by literature study using model of the statute approach, conceptual approach, and historical approach. The results show that at least there are efforts to weaken the KPK, including legitimacy that degrades the independence of the KPK through the enactment of Law Number 19 of 2019 concerning the Corruption Eradication Commission. It is known that there was a technical action that should have been regulated in the implementing regulations, but it has been sufficiently touched on by the legislation of the Corruption Eradication Commission (KPK).